ChemInform Abstract: Enantioselective Synthesis of Functionalized Quaternary Stereocenters. Issue 5 (January 2016) - Manchoju, Amarender; Thorat, Rakesh G.; Pansare, Sunil V.
Abstract: The target products (V) and (IX) are obtained through a stereoselective Suzuk—Miyaura cross‐coupling reaction giving disubstituted alkylidenemorpholinones (III) and (VIII) followed by a highly stereoselective Prins reaction.